Potential therapeutic effects and pharmacological evidence of sinomenine in central nervous system disorders - Hong, Hongxiang; Lu, Xu; Lu, Qun; Huang, Chao; Cui, Zhiming (Frontiers in Pharmacology, 2022)
Sinomenine is a natural compound extracted from the medicinal plant Sinomenium acutum. Its supplementation has been shown to present benefits for in a variety of animal models of central nervous system (CNS) disorders, such as cerebral ischemia, intracerebral hemorrhage, traumatic brain injury (TBI), Alzheimer’s disease (AD), Parkinson’s disease (PD), epilepsy, depression, multiple sclerosis, morphine tolerance, and glioma. Therefore, sinomenine is now considered a potential agent for the prevention and/or treatment of CNS disorders. Mechanistic studies have shown that inhibition of oxidative stress, microglia- or astrocyte-mediated neuroinflammation, and neuronal apoptosis are common mechanisms for the neuroprotective effects of sinomenine. Other mechanisms, including activation of nuclear factor E2-related factor 2 (Nrf2), induction of autophagy in response to inhibition of protein kinase B (Akt)-mammalian target of rapamycin (mTOR), and activation of cyclic adenosine monophosphate-response element-binding protein (CREB) and brain-derived neurotrophic factor (BDNF), may also mediate the anti-glioma and neuroprotective effects of sinomenine. Sinomenine treatment has also been shown to enhance dopamine receptor D2 (DRD2)-mediated nuclear translocation of αB-crystallin (CRYAB) in astrocytes, thereby suppressing neuroinflammation via inhibition of Signal Transducer and Activator of Transcription 3 (STAT3). In addition, sinomenine supplementation can suppress N-methyl-D-aspartate (NMDA) receptor-mediated Ca2+ influx and induce γ-aminobutyric acid type A (GABAA) receptor-mediated Cl- influx, each of which contributes to the improvement of morphine tolerance and sleep disturbance. In this review, we outline the pharmacological effects and possible mechanisms of sinomenine in CNS disorders to advance the development of sinomenine as a new drug for the treatment of CNS disorders.